Development Snack Bar Composite Flour of Goroho Banana (Musa Acuminata), Purple Yams (Ipomoea Batatas L.) And Green Bean (Vigna Radiata) - Erny J.N. Nurali; Eka T. P. Ruindungan; Mercy I.R. Taroreh; Dekie Rawung; Joachim J. E. Ossoe (Jurnal Agroekoteknologi Terapan, 2023)
Snack bars are an emergency food source of energy because they contain sufficient calories and complete nutrition. The purpose of this research is to (1) Analyzed the nutritions content (moist, ash, protein, fat, carbohydrate dan crude fiber) of the snack bar made from composite flour of goroho plantain, purple sweet potato, and mung beans, (2) evaluate the sensory preferences of snack bars which is made from composite flour of goroho plantain, purple sweet potato, and mung beans preferred. This research was used a completely randomized design (CRD) with various treatments of goroho banana flour, purple sweet potato flour, mung bean flour, namely A (25% : 45% : 30%), B (35% : 35% : 30%) , C (45% : 25% 30%), D (55% : 15% : 30%). The result showed that the nutritional content of the composite flour snack bar of goroho plantain, purple sweet potato, and green beans have an average value of moist (11.82% - 15.09%), ash (2.31% - 3.03%) , protein (10.96% - 12.71%), fat (8.23% - 8.99%), carbohydrates (62.63% - 63.86%), crude fiber (2.17% - 3.15%) and total calories 375,5 kkal – 383,39 kkal with a preference for color is 4.58 - 5.3 (slightly like), aroma is 4.70 - 4.84 (slightly like), taste is 4.17 - 4.96 (neutral - moderately like), and texture is 3.60 – 4.41 (neutral). Keywords: Snack bar, Goroho Plantain Flour, Purple Sweet Potato Flour, Mung Bean Flour . Abstrak Snack bar merupakan pangan darurat sumber energi karena mengandung kalori yang cukup dan gizi yang lengkap. Tujuan penelitian ini untuk (1) menganalisis kandungan gizi (kadar air, kadar abu, kadar protein, kadar lemak, kadar karbohidrat, kadar serat kasar dan total kalori) snack bar tepung komposit pisang goroho, ubi jalar ungu dan kacang hijau (2) mengevaluasi tingkat kesukaan produk snack bar tepung komposit pisang goroho, ubi jalar ungu dan kacang hijau. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan perlakuan variasi tepung pisang goroho, tepung ubi jalar ungu, tepung kacang hijau, yaitu A (25% : 45% : 30%), B (35% : 35% : 30%), C (45% : 25% 30%), D (55% : 15% : 30%). Hasil kandungan gizi snack bar tepung komposit pisang goroho, ubi jalar ungu, dan kacang hijau memiliki nilai rata-rata yaitu kadar air (11,82% - 15,09%), kadar abu (2,31% - 3,03%), kadar protein (10,96% - 12,71%), kadar lemak (8,23% - 8,99%), karbohidrat (62,63% - 63,86%), serat kasar (2,17% - 3,15%) dan total kalori 375,5 kkal – 383,39 kkal dengan tingkat kesukaan terhadap warna 4,58 - 5,3 (agak suka), aroma 4,70 - 4,84 (agak suka), rasa 4,17 - 4,96 (netral - agak suka), dan tekstur 3,60 – 4,41 (netral). Kata kunci: Snack Bar, Tepung Pisang Goroho, Tepung Ubi Jalar Ungu, Tepung Kacang Hijau